OC-045 Antroduodenal manometry: impact on clinical management. (23rd September 2015) - Mahesh, V N; Unsworth, B; Wrightham, E; Lal, S; Mclaughlin, J; Shaffer, J; Paine, P
Abstract : Introduction: Antroduodenal Manometry (ADM) is a key tool in the characterisation of upper gut motility.1 However the technique is not widely employed in the UK and data demonstrating the impact of short-term stationary manometry on clinical management are sparse. Aim: To evaluate the clinical outcome and impact of short-term stationary ADM in patients with suspected upper gut dysmotility in a tertiary hospital. Methods: A retrospective review of all patients undergoing ADM between August 2006 to November 2009 was conducted. After an overnight fast a single water perfused catheter with 8 sensors was passed per nares to 90 to 110 cms, with the flow rate controlled at 0.4 ml/min/sensor. Migrating Motor Complexes (MMC) and phase 1, 2 and 3 contractions were recorded in the fasted state (3 h), then post prandially following a standard feed (Ensure Plus 220 ml; 1–2 h). Parameters included frequency, amplitude and propagation. Results: 55 patients were included (43 female (78%), 12 male (22%), mean age 43 years, range 18–75). Eleven were external referrals solely for this investigation so complete clinical records were available in 44 patients. Their predominant symptoms were persistent nausea and vomiting in 28 (51%); abdominal pain in 10 (18%), distension 5 (9%) and others 12 (22%) including constipation, diarrhoea, early satiety, intolerance to enteral tube feeds. Clinical indications for the study were primarily diagnostic in 49 (89%), subclassification of known dysmotility in 2 (4%) and assessment for generalised dysmotility in patients with colonic dysmotility 4(7%). ADM was abnormal in 34 (62%) patients. Abnormal findings were most common in patients with persistent nausea and vomiting (19/28, 68%), abdominal pain (6/10, 60%) and colonic dysfunction (3/5, 60%). Key manometric diagnoses are presented in Abstract 045 . In patients with complete data (n=44), the manometric findings led directly to a positive change in management in 28 (64%), including commencement of a liquid diet (n=6), initiation (n=3) or withdrawal (n=2) of enteral tube feeding, initiation and/or continuation of total parenteral nutrition (n=6), or avoidance of colonic surgery (n=2). Conclusion: Short term, stationary manometry influences diagnosis and management of refractory symptoms such as persistent nausea and vomiting and abdominal pain, and is particularly helpful in shaping nutritional management decisions. Whether its utility can be improved in this difficult patient group by using 24 hour ambulatory or high-resolution techniques therefore warrants further exploration.